Feasibility Study of Company Investment on Public Cigarette Manufacturing Companies - Syamsul Huda; Heikal Muhammad Zakaria Hakim (Integrated Journal of Business and Economics (IJBE), 2019)
The number of tobacco manufacturing companies is decreasing significantly, above 60 (sixty) companies on average every year. However, the cigarette companies contribute a significant amount to the state revenues, with an increase of more than 5 (five) trillion rupiah every year. Based on the data, we want to know the feasibility of investing in a cigarette company in the future. The method used includes four stages starting from data collection, data analysis, preliminary data processing, and concluding. This research use three sample companies: PT. Bentoel Internasional Investama Tbk, PT. Gudang Garam Tbk, and PT. HM Sampoerna Tbk. The results showed that based on the ROI, NPV, IRR, and BEP, PT. Gudang Garam Tbk. is the most feasible, followed by PT. HM Sampoerna Tbk. Meanwhile, PT. Bentoel Internasional Investama Tbk not feasible for investment.